ANAESTHESIA FOR INTERVENTIONAL NEURORADIOLOGY - Ahmed, Aliya (Journal of Ayub Medical College Abbottabad, 2007)
There have been rapid and significant advances in diagnostic and interventional radiology, including interventional neuroradiology, in recent years. Many intracranial vascular pathologies are being successfully managed by endovascular interventional neuroradiology techniques. These techniques include procedures like embolization of vascular tumours and arterio-venous malformations, coiling of cerebral aneurysms, etc. The support of anaesthesia team is requested for these therapeutic endovascular neuroradiological procedures. The main aims of the anaesthesiologist during any interventional neuroradiology procedure are provision of a physiologically stable and immobile patient, alteration of arterial blood pressure as necessary, and appropriate and timely management of complications. Provision of anaesthesia in remote locations, such as the radiology suite, has its own inherent risks. In this article the anaesthetic considerations for therapeutic interventional neuroradiology procedures performed in the radiology suite have been reviewed, including the preprocedure preparation, monitoring requirements, suitable anaesthetic techniques, postprocedure management and complications. Key Words: Anaesthesia; Neuroradiology; Interventional radiolo gy